Brief Review of Sub-Kelvin Refrigeration Technology - Dai Wei; Pan Teng; Zhao Peng; Cheng Weijun (Zhileng xuebao)
Sub-Kelvin refrigeration technology (<1 K) is a critical supporting technology for cutting-edge physics research and quantum technology. Currently, it mainly includes adsorption refrigeration, dilution refrigeration, and adiabatic demagnetization refrigeration. Adsorption refrigeration is limited by its evaporative cooling principle, with the lowest temperature higher than 200 mK. Dilution refrigeration and adiabatic demagnetization refrigeration can achieve temperatures below 10 mK. The former can provide a larger continuous cooling capacity between 20 mK and 100 mK, while the latter, based on solid-state refrigeration, can operate efficiently under a microgravity environment. This article briefly introduces the principles, development history, and technical prospects of these three technologies.